Effect of type 2 diabetes on biochemical markers of bone metabolism: a meta-analysis - Yang, Jie; Zhang, Yuan; Liu, Xiaohua; Chen, Binglin; Lei, Le (Frontiers in Physiology, 2024)
Objective: This meta-analysis aims to examine differences in biochemical markers of bone metabolism between individuals with type 2 diabetes (T2DM) and non-T2DM control groups.Materials and Methods: Two independent evaluators searched five databases: PubMed, EMBASE, EBSCOhost, Web of Science, and the Cochrane Library. We aimed to identify observational studies investigating the impact of T2DM on biochemical markers of bone metabolism. Literature retrieval covered the period from the establishment of the databases up to November 2022. Studies were included if they assessed differences in biochemical markers of bone metabolism between T2DM patients and non-T2DM control groups using cross-sectional, cohort, or case-control study designs.Results: Fourteen studies were included in the analysis, comprising 12 cross-sectional studies and 2 cohort studies. Compared to the non-T2DM control group, T2DM patients showed reduced levels of OC and P1NP, which are markers of bone formation. Conversely, levels of ALP and BSAP, other bone formation markers, increased. The bone resorption marker CTX showed decreased levels, while TRACP showed no significant difference.In individuals with T2DM, most bone turnover markers indicated a reduced rate of bone turnover. This reduction can lead to increased bone fragility despite higher bone mineral density, potentially increasing the risk of osteoporosis.